Alloimmunization in dogs after transfusion: A serial cross‐match study. (19th August 2022) - Herter, Lisa; Weingart, Christiane; Merten, Nina; Bock, Nicole; Merle, Roswitha; Kohn, Barbara
Abstract: Background: Cross‐matching is performed to determine the serological compatibility of donor and recipient blood. Current guidelines recommend that cross‐matching should be performed in dogs when an initial transfusion was performed more than 4 days ago or when the transfusion history is unknown. Hypothesis: Determination at what time point alloantibodies are detected in dogs after transfusion. The hypothesis was that dogs would form alloantibodies within 4 days after a transfusion. Animals: Twenty‐one anemic dogs were transfused and monitored for at least 4 subsequent days. Exclusion criteria were persistent red blood cell (RBC) agglutination and a previous transfusion. Methods: Prospective observational study. Cross‐matching was performed before the initial DEA 1‐compatible transfusion and on days 1, 2, 3, and 4 and if possible, between day 5 and 28, using the tube method without enhancement (major cross‐match, recipient controls); recipients were monitored for transfusion reactions. Results: In 12/21 dogs a positive cross‐match (microscopic degree of agglutination [AD] 1+ to 2+) was observed within 4 days after the transfusion. In a nonlinear regression model, no significant association was detected between type of anemia ( P  = .41), RBC storage time ( P  = .44), immunosuppressive treatment ( P  = .75) nor transfusion volume ( P  = .70) and the occurrence of positive cross‐matches within 4 days after transfusion. Another 4 dogs developed a positive cross‐match (microscopic AD 1+ to 2+) after 6 to 13 days. Conclusions and Clinical Importance: Because production of alloantibodies was detected as early as 1 day after transfusion, cross‐matching should be performed before every subsequent transfusion.